El manejo de los bosques tropicales: retos, deficiencias y oportunidades - Putz, F.E. (1998)
Despite the challenges and deficiencies tropical forest research faces, it has never had so much power as now. Foresters rely on new approaches to stimulate a change in the way forest is used for a more sustainable management system. In addition, new legislation and international agreements on forests will help if there is political willingness to apply the laws and postpone economic benefits. However, before there is any possibility of change from the culture of forest exploitation to the culture of forest management, it is necessary to address some issues. Some lumbermen, forest concessionaires and forest owners do not see any reason to change the present exploitation practices; they argue that they have no access to the information for implementation of reduced impact logging techniques and other forest management practices; and additionally forest management is less profitable in the short-term. There is a need to respond to these issues, to accept the challenges and to overcome the deficiencies in the research programmes to stop destructive forest exploitation practices and preserve the forest.